Diagnóstico socioeconómico Post Covid-19 del comercio formal del mercado Colón, cantón Milagro, Ecuador 2023 - Bajaña Jiménez, Génesis Carolina (2023)
His scientific research contains a detailed analysis of the socio-economic situation of the Formal Trade of the Mercado Colón in the city of Milagro, Province of Guayas. The main objective of this study consisted in diagnosing the postCOVID-19 socio-economic situation in the formal commerce of the Mercado Colon belonging to the Milagro Canton, through the preparation of a socioeconomic diagnosis that allowed evaluating their behavior. The methodology used during the development of the research was a mixed approach (qualitative - quantitative), with a type of research with a descriptive scope, the inductive - deductive and statistical methods were used for the analysis and interpretation of the results, managing to establish the quantity and quality the interpretation of data obtained from surveys and interviews. From the analysis of results, the socio-economic situation of the business owners of the premises of the Formal Trade of the Mercado Colón, Milagro was determined; through surveys and interviews. The most relevant information obtained was the social, economic and financial data, especially those referring to education, social status, seniority in the business, financial data related to income and expenses, and other information of a social, economic and financial nature. In addition, the absence of not having social or medical insurance, and the lack of educational levels, among other relevant aspects. Conclusions: This work allowed to establish the socio-economic situation of the merchants of the Formal Trade of the Mercado Colón, Milagro; determine through a SWOT Matrix the strengths, opportunities, weaknesses and threats resulting from this study, as well as its conclusions and recommendations.